Peningkatan Kompetensi Guru Profesional melalui Program Praktik Mengajar di Perguruan Tinggi Keagamaan Islam Swasta - Uswatun Hasanah; Sheila Rosmalinda; Moh. Wardi (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2022)
This study aims to describe teaching practice programs as a way to improve teachers' professional competence in private Islamic higher education. This study uses a descriptive qualitative approach with data collection methods through observation, interviews, and documentation. Researchers used technical triangulation through interviews and then compared with observational data and documentation. The study results found that the teaching practice program is mandatory and lasts one year. The activity system has been designed and structured. The implementation of the teaching practice program must be balanced with the guidance, coaching, and direction held regularly every week. Competencies acquired through teaching practice programs include several types of competencies: personal, pedagogical, social, and professional.